Endogenous Mobilization of Mesenchymal Stromal Cells: A Pathway for Interorgan Communication? - Girousse, Amandine; Mathieu, Maxime; Sastourné-Arrey, Quentin; Monferran, Sylvie; Casteilla, Louis; Sengenès, Coralie (Frontiers in Cell and Developmental Biology, 2021)
To coordinate specialized organs, inter-tissue communication appeared during evolution. Consequently individual organs communicate their states via a vast interorgan communication network (ICN) made up of peptides, proteins and metabolites that act between organs to coordinate cellular processes under homeostasis and stress. However, the nature of the interorgan signalling could be even more complex and involve mobilization mechanisms of unconventional cells that are still poorly described. Mesenchymal stem/stromal cells (MSCs) virtually reside in all tissues though the biggest reservoir discovered so far is adipose tissue where they are named adipose stromal cells (ASCs). MSCs are thought to participate to tissue maintenance and repair since the administration of exogenous MSCs is well known to exert beneficial effects under several pathological conditions. However, the role of endogenous MSCs is barely understood. Though largely debated, the presence of circulating endogenous MSCs has been reported in multiple pathophysiological conditions but the significance of such cell circulation is not known and therapeutically untapped. In this review we discuss current knowledge on the circulation of native MSCs and we highlight recent findings describing MSCs as putative key components of the ICN.